2005
DOI: 10.1242/jcs.02625
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine and calcium signalling regulates muscle fibre formation in the zebrafish embryo

Abstract: Nerve activity is known to be an important regulator of muscle phenotype in the adult, but its contribution to muscle development during embryogenesis remains unresolved. We used the zebrafish embryo and in vivo imaging approaches to address the role of activity-generated signals, acetylcholine and intracellular calcium, in vertebrate slow muscle development. We show that acetylcholine drives initial muscle contraction and embryonic movement via release of intracellular calcium from ryanodine receptors. Inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
89
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(106 citation statements)
references
References 53 publications
15
89
1
1
Order By: Relevance
“…4B). We followed the protocol described by Brennan et al (2005), and calculated the duration as the time taken for a signal to decay from the maximum amplitude to half of that value. Fig.…”
Section: Characterizing the Trunk Ca 2+ Signals In Zebrafish With Aeqmentioning
confidence: 99%
See 4 more Smart Citations
“…4B). We followed the protocol described by Brennan et al (2005), and calculated the duration as the time taken for a signal to decay from the maximum amplitude to half of that value. Fig.…”
Section: Characterizing the Trunk Ca 2+ Signals In Zebrafish With Aeqmentioning
confidence: 99%
“…Li et al (2004) then reported that spontaneous Ca 2+ signals appear to regulate patterned actin assembly during myofibrillogenesis in cultured Xenopus myocytes, where blocking these signals disrupted the assembly of the actin thin filaments and the actinassociated z-disc affiliated proteins, titin and capZ. More recently, Brennan et al (2005) reported that in intact zebrafish embryos, the release of intracellular Ca 2+ from RyRs drives the initial contraction of slow muscle cells (SMCs) and that these contractions are responsible for the embryonic movements that occur at 17 -22 hpf. They also reported that this process is regulated by acetylcholine and results from spontaneous neuronal activity.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations